Analisis Kepuasan Pelayanan Kefarmasian Pada Pasien Rawat Jalan di Rumah Sakit Rupit Kabupaten Musi Rawas Utara Tahun 2026 - Rifka Faisal; Arie Wahyudi; Chairil Zaman (JURNAL KESEHATAN TERAPAN, 2026)
Pharmaceutical services are an integral part of healthcare services that are patient-oriented and aimed at improving service quality and patients' quality of life. Patient satisfaction is one of the essential indicators used to assess the quality of pharmaceutical services. This study aimed to analyze pharmaceutical service satisfaction among outpatients at Rupit Regional General Hospital, Musi Rawas Utara Regency, in 2026 and to identify factors associated with patient satisfaction. This study employed a quantitative method using an analytical survey design with a cross-sectional approach. The study population consisted of 1,062 patients who obtained medications from the hospital pharmacy installation during November–December 2025 and January 2026. A total of 291 respondents were selected using a random sampling technique based on Slovin's formula. Data were analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using multiple logistic regression. There were significant associations between education p-Value 0,006 (OR=0,495 dan CI=0,298-0,823), knowledge p-Value 0,005 (OR=0,1,971 dan CI=1,223-3,175), tangibles p-Value 0,000 (OR=37,53 dan CI=17,928-78,601), reliability p-Value 0,000 (OR=156,75 dan CI=62,430-393,56), responsiveness p-Value 0,00 (OR=31,01 dan CI=16,31-58,95), assurance p-Value 0,000 (OR=18,68 dan CI=10,27-34,003) and empathy p-Value 0,000 (OR=178,875 dan CI=42,234-757,602) with patient satisfaction of pharmaceutical services. No significant associations were found between gender (p-value 0,529), age (p-value 0,949) and employment status (p-value 0,884) and patient satisfaction. The findings of this study are expected to provide an overview of the level of patient satisfaction and identify the most dominant factors associated with satisfaction with pharmaceutical services. Furthermore, the result are expected to rserve as evaluation material and a basic for policy-making to improve the quality of pharmaceutical services at RSUD Rupit.